1996
DOI: 10.1016/0014-5793(95)01529-9
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of secretolytin, a chromogranin B‐derived peptide (614–626), is correlated with peptide structure

Abstract: Amongst the chromogranin B (CGB) derived fragments naturally generated in bovine chromaffin granules and detected in the extracellular space, we recently identified a major peptide corresponding to the 614--626 sequence of CGB. This peptide, named secretolytin, shared an interesting sequence homology with the lyric domain of cecropins and displayed a potent antibacterial activity. The aim of the present study was to determine the structural features of secretolytin necessary for this biological activity. Our r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 36 publications
2
27
0
Order By: Relevance
“…Interestingly, the main cleavage site in position 78-79 of bCGA and the subsequent remove of the two basic residues K77 and K78 by the carboxipeptidase H (Metz-Boutigue et al, 1993) produces two antimicrobial fragments: vasostatin-I (VS-I; bCGA1-76) (Lugardon et al, 2000) and prochromacin (Prochrom; bCGA79-431) (Strub et al,1996b). For these N-and C-terminal domains with antimicrobial activities several shorter active fragments were identified: for VS-I, bCGA1-40 (N CgA; NCA) (Shooshtarizadeh et al, 2010), bCGA47-66 (chromofungin; CHR) and for ProChrom, bCGA173-194 (Chromacin; Chrom) (Strub et al, 1996b) and bCGA344-364 (Catestatin; CAT) (Shooshtarizadeh et al, 2010). The unique disulfide bridge of bCGA is present in VS-I and NCA sequences.…”
Section: Antimicrobial Peptides Derived From Chromogranin Amentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the main cleavage site in position 78-79 of bCGA and the subsequent remove of the two basic residues K77 and K78 by the carboxipeptidase H (Metz-Boutigue et al, 1993) produces two antimicrobial fragments: vasostatin-I (VS-I; bCGA1-76) (Lugardon et al, 2000) and prochromacin (Prochrom; bCGA79-431) (Strub et al,1996b). For these N-and C-terminal domains with antimicrobial activities several shorter active fragments were identified: for VS-I, bCGA1-40 (N CgA; NCA) (Shooshtarizadeh et al, 2010), bCGA47-66 (chromofungin; CHR) and for ProChrom, bCGA173-194 (Chromacin; Chrom) (Strub et al, 1996b) and bCGA344-364 (Catestatin; CAT) (Shooshtarizadeh et al, 2010). The unique disulfide bridge of bCGA is present in VS-I and NCA sequences.…”
Section: Antimicrobial Peptides Derived From Chromogranin Amentioning
confidence: 99%
“…It is well conserved during evolution and is homologous to the C-terminal sequence of CGB and the antibacterial peptide SEC (secretolytin) [(Strub et al, 1996b). This peptide was generated in vitro after digestion, by the protease Glu-C from S. aureus, of the material present in chromaffin secretory vesicles.…”
Section: C-terminal Cga-derived Fragmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings may indicate that vasostatin is a new active component in innate immunity (105). Glycosylated and phosphorylated CgA-derived peptide (bovine adrenal) show antibacterial activity (106) and CgB-derived peptide, secretolytin, also exhibits antibacterial activity (107). Further, the C terminal of proenkephalin-A-derived peptide possesses anti-bacterial potency (108).…”
Section: Chromograninmentioning
confidence: 99%
“…Since 1995, we have shown that antibacterial activities are present within the intragranular chromaffin granule matrix and are recovered in the extracellular medium following secretion. This activity has been assigned to chromogranin A and B fragments and PEAPs (4,(12)(13)(14)(15)(16)(17). Among the intragranular matrix components, enkelytin, an antibacterial peptide corresponding to the bisphosphorylated fragment PEAP209 -237, was identified (14).…”
mentioning
confidence: 99%